Development of efficient micropropagation protocol of Dendrocalamussp. using temporary immersion bioreactor system for commercial large-scale production - Yasamut, Amonrat; Thongrote, Chananbhorn; Wongchaya, Panuphon; Bansra, Tatiya; Teeraarunsiri, Kornkanok; Moolinta, Saksun; Chaisan, Wararith; Mahadtanapuk, Supuk (Agriculture and Natural Resources, 2026)
Importance of the work: Dendrocalamus sp. is a valuable Thai bamboo with high demand. Micropropagation ensures rapid, efficient plantlet production to fulfill supply requirements. Objectives: To optimize Dendrocalamus sp. micropropagation using temporary immersion bioreactor (TIB) technology and plantlet acclimatization. Materials and Methods: In vitro techniques were used to develop a micropropagation protocol. Various Murashige and Skoog (MS) medium treatments with different plant growth regulator combinations were tested to determine the optimal concentrations for explant growth. Results: Semi-solid MS medium with 3 mg/L 6-benzylaminopurine (BAP) and 2 mg/L α-naphthalene acetic acid (NAA) produced the highest shoot induction, averaging 24.66 shoots per explant. In addition, the TIB was used for increasing production. The method showed that a feeding frequency of 2 hr in the same medium containing 500 mL to initiate 10 explants produced the significantly highest number of shoots (72.33 shoots per bottle) of all the tested conditions. The survival rate was 99% across all substrates for both the greenhouse and field conditions. Based on morphological studies, there were no differences between the donor mother plants and the regenerated plants. These findings highlighted the effectiveness of this micropropagation protocol for large-scale bamboo production, making it a reliable method for commercial propagation of Dendrocalamus sp. Main finding: MS medium with 3 mg/L BAP and 2 mg/L NAA optimized Dendrocalamus sp. growth, ensuring 99% survival and no morphological changes. This procedure enhanced propagation efficiency, producing 1,382 times more plants than stem cutting for large-scale cultivation.